West Africa Presidential Elections 2024Case Study (Senegal and Mauritania) (قضايا سياسية, 2024)
The presidential elections in the West African region of Senegal and Mauritania were characterized by a democratic atmosphere, despite the problems that accompanied the electoral process before and after, in addition to the turbulent regional atmosphere characterized by the intensification of the conflict between international powers. The opposition candidate in Senegal (Passirou Diomaye Faye) was able to win in the first round, and this also applies to the victory of (Mohamed Ould Cheikh El Ghazouani) in deciding the competition in his favor in the presidential elections for a second term. Both countries face common internal and external challenges represented by the security challenge and the fight against rampant corruption in all aspects of the state, in addition to the political and economic reforms that the leaders of the two countries promised during the election campaign. The leaders of those countries also seek to liberate themselves from French dependency.